The Legal Status of Azov Sea and the Kerch Strait: Ukraine v. Russia - Astutik, Zulfiani Ayu; Özaltın, Mert Ahmet (Indonesian Comparative Law Review, 2021)
The Black Sea has been the scene of conflict between coastal states throughout history. Recently, emerging Russia-Ukraine tension continues. The Russian Federal Security Service ("FSB") destroyed and captured three Ukrainian Military Ships and detained 24 of its personnel on November 23, 2018. As the dispute continued, Ukraine finally raised the matter to the International Tribunals on Law of The Sea ("ITLOS"). This tension, which reaches a hot conflict point from time to time, causes legal changes in the Black Sea eventually. This article discusses the current legal status of Crimea, the Sea of Azov, and the Kerch Strait and aims to explain from the perspective of Russia, Ukraine, and Turkey. The study shows how the conflict environment in the region has a changing effect on the existing maritime borders and whether Russia’s act is a part of violation of the UNCLOS and International Law.